Remarks about the eilenberg-zilber type decomposition in cosimplicial sets (1978)
Contents §O Introduction §1 Sections and retractions in the category  ∆. §2 Adjoints of morphisms in the category  ∆. §3 Conditions fo~ unicity of the Eilenberg-Zilber type decomposition in co-simplicial sets. §4 Stability of interior points for co-degeneracies.